Synthesis, spectral analysis, molecular docking and biological evaluation of cyclohepta[b]indole derivatives - Pandian Amuthavalli, Ayyachamy (Array, 2019)
A new series of specifically substituted cyclohepta[b]indole derivatives from the precursor thiophen-2-ylmethylene has been synthesized. The structures of synthesized derivatives were established by spectral and elemental analyses. The docking studies with protein kinase CK2 was performed, derivative 6c exhibited the most excellent glide and E model score of –7.61 and –58.27, respectively. In-vitro anticancer activity against cervical cancer cell line (HeLa) was studied. The IC50 values were compared with the standard drug Ellipticine. Compounds 5c, 6c and 6d showed better IC50 value when compared to the other molecules. The derivatives were evaluated for their antibacterial activity against the reference drugs Sparfloxacin and Norfloxacin using agar dilution method. The derivatives 4a–d exhibited better MIC values against Gram-positive bacteria and Gram-negative bacteria when compared with remaining derivatives. Structure activity relationship (SAR) analyses established that the derivatives are potential lead compounds for future drug development studies.